Toxin gene profiling of methicillin-susceptible Staphylococcus aureus (MSSA) isolated from a Malaysian teaching hospital - Neoh, Hui-min; Saberi Saimun,; Hassriana Fazilla Sapri,; Salasawati Hussin,; Rahman Jamal, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Entero- and exfoliative toxin gene profiling of 237 methicillin-susceptible Staphylococcus aureus (MSSA) isolated from Universiti Kebangsaan Malaysia Medical Centre (UKMMC) were carried out via PCR amplification. Among the tested toxin genes, sei was found to be the most prevalent (54.9%).